The Anti-proliferative Activity of GnRH Through Downregulation of the Akt/ERK Pathways in Pancreatic Cancer - Suo, Linna; Chang, Xiaocen; Xu, Na; Ji, Hongmei (Frontiers in Endocrinology, 2019)
Gonadotropin-releasing hormone (GnRH) has been demonstrated to exert anti-proliferative functions on various tumor cells in endometrial, ovarian, bladder, or prostate cancer as a part of the autocrine system. In addition, the expression levels of GnRH and its receptor had been identified in breast cancer or non-reproductive cancers, such as glioblastoma and pancreatic cancer. Previous studies have reported abnormal GnRH expression in several malignant tumors, suggesting that GnRH and its receptor might be essential for tumourigenesis. In the present study, we attempted to clarify the mechanisms underlying GnRH function in cell proliferation in pancreatic cancer. Our results indicated that GnRH expression might be essential for the malignancy of pancreatic cancer. We then found that GnRH overexpression can induce cell apoptosis through activating the Bcl-2/Bax pathway and autophagy might be involved in the GnRH-mediated apoptosis in Panc1 cells. Further investigation showed that the inhibition of GnRH may promote tumor invasion and migration through upregulation of MMP2 expression in pancreatic cancer cells. Moreover, our results indicated that GnRH can regulate the Akt/ERK1/2 pathways to promote cell proliferation by inhibiting cell apoptosis in Panc1 cells. Therefore, our finding exhibited that the regulation of GnRH expression may be essential for tumourigenesis in pancreatic cancer, and might be a potential target for the treatment of the patients with pancreatic cancer.